2017
DOI: 10.1158/0008-5472.can-17-0709
|View full text |Cite
|
Sign up to set email alerts
|

Raman-Encoded Molecular Imaging with Topically Applied SERS Nanoparticles for Intraoperative Guidance of Lumpectomy

Abstract: Intraoperative identification of carcinoma at lumpectomy margins would enable reduced re-excision rates, which are currently as high as 20–50%. While imaging of disease-associated biomarkers can identify malignancies with high specificity, multiplexed imaging of such biomarkers is necessary to detect molecularly heterogeneous carcinomas with high sensitivity. We have developed a Raman-encoded molecular imaging (REMI) technique in which targeted nanoparticles are topically applied on excised tissues to enable r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(101 citation statements)
references
References 54 publications
2
99
0
Order By: Relevance
“…This imaging method is only applicable to the tissue surface, thus, it is not able to tell if margins are clear 2 mm below the surface for DCIS. 114 REMI is attractive as a technology for use in identifying positive margins since it gives relevant biological information in these biomarkers. It does suffer from the need for use of applied nanoparticles and long scan times.…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…This imaging method is only applicable to the tissue surface, thus, it is not able to tell if margins are clear 2 mm below the surface for DCIS. 114 REMI is attractive as a technology for use in identifying positive margins since it gives relevant biological information in these biomarkers. It does suffer from the need for use of applied nanoparticles and long scan times.…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…However, no single or "perfect" tumor-specific marker has been identified that would be overexpressed by all cancer types, although it is possible to combine multiple biomolecule vectors (target markers) 4 or multiple imaging agents. 5…”
Section: Dear Editormentioning
confidence: 99%
“…12,13 Rates of reexcision vary but it is reported that between 20% and 50% of patients undergo additional surgery when final surgical resection pathology demonstrates positive or close margins. 14,15 To reduce the need to return to the operating room, a number of ex vivo imaging techniques including surface enhanced Raman scattering nanoparticles 16,17 and intrinsic Raman spectroscopy, [18][19][20] optical coherence tomography, 21,22 and confocal 23 and light reflectance spectroscopy 24,25 have been explored for their intraoperative use in breast margin assessment. These techniques have been developed to image the tissue at margin in real time with the hope of detecting tumor present adjacent to margin during surgery.…”
Section: Arch Pathol Lab Med-vol 143 September 2019mentioning
confidence: 99%